Corruption Hand Capture Operation (OTT) On Illegal Payments of Recommendation Permit Application Development In Telecommunication Tower Construction - Wachid Aryanto; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
This article aims to identify and analyze the corruption of extortion through hand operation to the request for consent on construction of telecommunication towers. The analysis in this study using the case study method, by understanding the phenomenon of corruption through hand operations in depth, exploring and elaboration. Results of research and discussion shows that reports of extortion became the basis for investigators to conduct hand operations. The investigation team was able to prove corruption based on the principle of legality and culpability laid down in Article 12 e of Act No. 20 of 2001 on Amendments to the Act No. 31 of 1999 on Corruption Eradication.Keywords: Corruption; Extortion; Hand Operations.